Editorial: Australia’s Social Media Ban for Under 16s - Holmes, Jim; Campbell, Leith H (Journal of Telecommunications and the Digital Economy, 2026)
Australia’s social media ban for minors under 16 years of age has been hailed as a world first and leading edge. Many other countries have shown interest and some have indicated that they will institute similar schemes. In this editorial, we reflect on the scheme after 3½ months of operation, considering the reported responses of social media firms and of users, and what might happen next. As an introduction to the March issue of the Journal, we outline the topics covered.